2005
DOI: 10.1037/0735-7044.119.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Aggression Are Differentially Related to Serotonergic Activity and the A779C TPH Polymorphism.

Abstract: The authors investigated whether different types of aggression relate to the A779C tryptophan hydroxylase (TPH) polymorphism and to serotonergic activity in volunteers. A factor analysis of the Buss-Durkee Hostility Inventory yielded 2 factors representing Neurotic Hostility (NH) and Aggressive Hostility (AH). The authors used a neuroendocrine challenge with Citalopram in 48 volunteers and increased cortisol concentrations only in those with high levels of AH. Finally, an association study with 58 volunteers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 55 publications
4
46
0
1
Order By: Relevance
“…The putative reason for an elevated cortisol response is an upregulation or sensitization of postsynaptic receptors, caused by a habitually diminished serotonin release (Hennig et al, 2005). Within this line of reasoning, our results support Depue's theory, which postulates that a reduced serotonergic functionality lowers the threshold for response elicitation, which, in turn, should manifest in temperamental traits (Depue and Collins, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…The putative reason for an elevated cortisol response is an upregulation or sensitization of postsynaptic receptors, caused by a habitually diminished serotonin release (Hennig et al, 2005). Within this line of reasoning, our results support Depue's theory, which postulates that a reduced serotonergic functionality lowers the threshold for response elicitation, which, in turn, should manifest in temperamental traits (Depue and Collins, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Survey studies (e.g., Hennig et al, 2005;R. Martin et al, 2000) have shown relations between Neuroticism and an angry type of aggression.…”
Section: Discussionmentioning
confidence: 99%
“…In a related study, Hennig et al [43] were able to identify variations of the tryptophan hydroxylase gene, which, if linked with specific individuals, could explain the lower levels of serotonin in the brain and thus account for heightened expressions of aggressive behavior. Indeed, utilizing healthy male subjects, these authors were able to identify several nucleotide polymorphisms of the tryptophan hydroxylase gene, one of which was then correlated with high levels of the aggressive hostility factor as determined from the Buss-Durkee and related inventory scales.…”
Section: Serotoninmentioning
confidence: 99%